The feudal order : state, society, and ideology in early medieval India - Jha, D N; Jha, D. N. (Dwijendra Narayan), 1940- (New Delhi : Manohar Publishers & Distributors, 2000)
Contributed articles.
Includes bibliographical references (p. [497]-526) and index.
Keywords: Social conflict -- India -- History; India -- Social conditions